Dynamic modelling and adaptive PID control of palm oil biodiesel engine - Azuwir, Mohd Nor (Universiti Malaysia Perlis (UniMAP), 2014)
The use of biodiesel seems set to become a popular alternative fuel for transportation to replace the high price petroleum fuel. To successfully implement the usage of biodiesel in transportation requires good understanding of the engine dynamics and reliable controller to manage the engine. Hence, this study is aimed at the development of mathematical models and adaptive controller of automotive engine fuelled with palm oil methyl esters (palm oil biodiesel). The process modelling investigation started with linear discrete-time single-input-single-output (SISO) dynamic mathematical models representing the relationship between engine speed and engine throttle of a diesel engine test-unit. Both deterministic and stochastic model types are derived and validated. Three parameter estimation techniques of Recursive Least Squares (RLS), Recursive Extended Least Squares (RELS) and Differential Evolution (DE) are used to estimate the engine parameters. Then, the nonlinear dynamic model of the engine type is derived and validated. Orthogonal Least Squares (OLS) estimation technique together with Error Reduction Ratio (ERR) procedures are used in the selection of the parsimonious model structure and parameter estimation for nonlinear ARX (NARX) model. The accuracy of linear and nonlinear dynamic models are compared and analyzed. The results show that all models derived are stable and good in predicting the engine output. Next, adaptive PID speed controller based on pole assignment method was designed, developed, tested and simulated before implemented in real-time on the engine test-unit. The adaptive controller is designed to track and regulate set-point speed as well as reject the disturbance introduced to the system. Throughout the investigation the control algorithm developed is tested at various engine set-point speeds and load disturbances. The results show that the algorithms produce very good dynamic output responses of the palm oil biodiesel engine. The algorithms have successfully achieved the control objective of tracking and regulating the engine speed. Furthermore, the experimental results also proved the disturbance rejection capability of the controller. The performance of the adaptive controller is compared with tracking, regulating and rejecting disturbance of automotive engine fuelled with petroleum diesel. In both cases, the controllers performed very well and proved to be reliable for both types of fuel. This study has significantly proved that adaptive PID speed controller developed performed effectively in controlling automotive engine speed fuelled with palm oil biodiesel and petroleum diesel without engine modification.